Development of a recombinant murine tumour model using hepatoma cells expressing hepatitis C virus nonstructural antigens. Issue 6 (21st February 2018) - Young, K. G.; Haq, K.; MacLean, S.; Dudani, R.; Elahi, S. M.; Gilbert, R.; Weeratna, R. D.; Krishnan, L.
Summary: Hepatitis C virus (HCV) chronically infects 2%‐3% of the world's population, causing liver disease and cancer with prolonged infection. The narrow host range of the virus, being restricted largely to human hepatocytes, has made the development of relevant models to evaluate the efficacy of vaccines a challenge. We have developed a novel approach to accomplish this by generating a murine hepatoma cell line stably expressing nonstructural HCV antigens which can be used in vitro or in vivo to test HCV vaccine efficacies. These HCV‐recombinant hepatoma cells formed large solid‐mass tumours when implanted into syngeneic mice, allowing us to test candidate HCV vaccines to demonstrate the development of an HCV‐specific immune response that limited tumour growth. Using this model, we tested the therapeutic potential of recombinant anti‐HCV‐specific vaccines based on two fundamentally different attenuated pathogen vaccine systems—attenuated Salmonella and recombinant adenoviral vector based vaccine. While attenuated Salmonella that secreted HCV antigens limited growth of the HCV‐recombinant tumours when used in a therapeutic vaccination trial, replication‐competent but noninfectious adenovirus expressing nonstructural HCV antigens showed overall greater survival and reduced weight loss compared to non‐replicating nondisseminating adenovirus. Our results demonstrate a model with anti‐tumour responses to HCV nonstructural (NS) protein antigens and suggest that recombinant vaccine vectors should be explored as a therapeutic strategy for controlling HCV and HCV‐associated cancers.